Microstructure and oxidation resistance of a NiCrAlY/Al2O3-sprayed coating on Ti-19Al-10Nb-V alloy. Issue 10 (1st August 2016) - Anghel, Elena Maria; Marcu, Maria; Banu, Alexandra; Atkinson, Irina; Paraschiv, Alexandru; Petrescu, Simona
Abstract: A Ti3 Al (α2 ) alloy (Ti-19Al-10Nb-3V, wt%) coated by air plasma spraying (APS) with Ni22Cr10AlY and Ni22Cr10AlY/Al2 O3 has been tested against cyclic oxidation in air at 850 °C for 10 cycles of 10 h each. Effects of pre-oxidation and cyclic oxidation treatments, both in air, on the microstructure of the single α2 /Ni22Cr10AlY and double coated α2 / Ni22Cr10AlY/Al2 O3 specimens were investigated by X-ray diffraction (XRD), SEM-EDS and Raman spectroscopy. Several distinct results appear through the cyclic oxidization of the pre-oxidized α2 / Ni22Cr10AlY, namely, elemental diffusion where Ti and Al diffuses from one side and Ni and Cr from the other side, oxygen is found to be present at the support-bond coat interface and a partial reaction of the superficial NiO with α-Al2 O3 to form the non-protective NiAl2 O4 takes place. Conversely, pre-oxidation treatment of the double coated α2 / Ni22Cr10AlY/Al2 O3 specimens causes transient alumina polymorphs obtained by APS to convert to α-Al2 O3 and hence to ensure the lowest cyclic oxidation rate seen by a k p value of 2.62×10 −12 g 2 cm −4 s −1 . Good adhesion to support of all the coated specimens is recorded following the cyclic oxidization treatment.